Optimization of Citric Acid Production by Substrate Selection Using Gamma Ray Induced Mutant Strain of Aspergillus niger (Global Journal of Medical Research, 2018)
The worldwide demand for citric acid is increasing with the rising population and industrialization. The growing demand for citric acid and the need for alternative materials as substrates in the recent years have led to the choice of a novel and economically viable substrate, namely jackfruit (outer portion) and molasses for citric acid biosynthesis. Hydrolysis these substrates with 0.05N HCl followed by fermentation using two isolates of Aspergillus niger were investigated for citric acid production under submerged culture condition in a period of 15 days. The products of the microbial metabolism namely residual sugar, total titratable acidity (TTA), citric acid, and biomass contents were determined periodically. Maximum citric acid production was found after 12 days of fermentation for both isolates, namely Aspergillus niger CA16, the parent strain and gamma ray induced mutant Aspergillus niger 79/20. Citric acid production was found highest in the absence of Prescott salt by Aspergillus niger CA16 in mixed fermentation medium which was about 16.35 mg/ml and lowest in jackfruit medium, 12.88 mg/ml at day 12. Whereas in the presence of Prescott salt, lowest citric acid production was also found in jackfruit medium, 7.21 mg/ml and highest in mixed medium, 11.54 mg/ml. In case of the previously isolated gamma-ray induced mutant Aspergillus niger 79/20, the yield seems to be higher under similar experimental condition.
Keywords: aspergillus niger 79/20; citric acid; titratable acidity